Multivisceral Resection of Advanced Pelvic Tumors: From Planning to Implementation - Mirnezami, R.; Mirnezami, A. (Clinics in Colon and Rectal Surgery, 2020)
Pelvic exenteration involves radical multivisceral resection for locally advanced and recurrent pelvic tumors. Advances in tumor staging, oncological therapies, preoperative patient optimization, surgical techniques, and critical care medicine have permitted the safe expansion of pelvic exenterative surgery at specialist units. It is now understood that in carefully selected patients, 5-year survival can exceed 60% following pelvic exenteration, and that very low mortality figures and an optimum postexenteration quality of life are possible. In the present review, we provide a contemporary summary of the current state of the art in pelvic exenterative surgery following all key phases of the treatment pipeline from patient staging and tumor assessment, to treatment planning and surgery.
Keywords: pelvic exenteration; multivisceral resection; advanced cancer; recurrent cancer